Strategi Dan Pendekatan Mengelola Konflik Di Lembaga Pendidikan Islam - Siti Fatimatus Zahro; Khoirotun Nisak; Retista Tammamy; Putri Yulianda; Rika Putri Sholiha; Mu’allimin Mu’allimin (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The innate human nature in social life is conflict, which if managed well, can serve as a catalyst for improving performance, particularly in Islamic educational institutions. This research examines strategies and approaches in conflict management, specifically within educational institutions. Overall, the importance of aligning conflict resolution theories with the unique characteristics of each conflict is emphasized. Specific conflict situations require appropriate resolution strategies, and often, failure to identify and assess conflicts is a primary cause of problems. Therefore, in Islamic educational institutions, there is a need for specialized skills in managing and diagnosing conflicts effectively, with the hope of developing effective conflict resolution strategies. This research utilizes a literature review methodology, where all information is derived from relevant articles and books.